Short Communication: Coral reef lifeform variation around power plant activity: Case study on coastal area of Paiton Power Plant, East Java, Indonesia - DIAN SAPTARINI; MUKHTASOR MUKHTASOR; INNEKE F.M. RUMENGAN (Society for Indonesian Biodiversity, 2017)
Abstract. Saptarini D, Mukhtasor, Rumengan IFM. 2017. Coral reef lifeform variation around power plant activity: Case study on coastal area of Paiton Power Plant, East Java, Indonesia. Biodiversitas 18: 116-120. Heat water, a waste, generated by industries activity near coastal area had generally higher temperature than sea water. It affected to marine organism which used coastal area as their habitat. Coral reefs as one of coastal productive ecosystem had stenotolerant adaptive nature. That nature made them relatively stay on narrow spanning upon environment changing factors. This study obtained to understand various composition of coral lifeform around steam power plant at district of Paiton in Probolinggo, East Java province. Both coral reef and water observed in five area based on distance of heat water distribution and coral presence. Line transect method was unfold in 30m for sampling. Certain parameter like coral coverage area, diversity, and water temperature were collect as data barrier factor for it presence. The percentage of coral coverage area resulted among 48.37-75.33%, it ranked at middle till good level. ANOVA analysis gave significant different toward inter-location coral lifeform and observation location. The ecosystem consisted as massive (CM), foliose (CF), encrusting (CE) and Acropora branching coral (ACB) were dominantly coral types who living over there. Keywords: Cooling water, coral branching, lifeform, temperature